Case Report: Atypical HUS Presenting With Acute Rhabdomyolysis Highlights the Need for Individualized Eculizumab Dosing - Benoit, Stefanie W.; Fukuda, Tsuyoshi; VandenHeuvel, Katherine; Witte, David; Fuller, Christine; Willis, Jennifer; Dixon, Bradley P.; Drake, Keri A. (Frontiers in Pediatrics, 2022)
Background: Atypical hemolytic uremic syndrome (aHUS) is an ultra-rare orphan disease caused by dysregulated complement activation resulting in thrombotic microangiopathy. Although complement-mediated endothelial injury predominantly affects the renal microvasculature, extra-renal manifestations are present in a significant proportion of patients. While eculizumab has significantly improved the morbidity and mortality of this rare disease, optimizing therapeutic regimens of this highly expensive drug remains an active area of research in the treatment of aHUS. Case Presentation: This report describes the case of a previously healthy 4 year-old male who presented with rhabdomyolysis preceding the development of aHUS with anuric kidney injury requiring dialysis. Clinical stabilization required increased and more frequent eculizumab doses compared with the standardized weight-based guidelines. In the maintenance phase of his disease, pharmacokinetic analysis indicated adequate eculizumab levels could be maintained with an individualized dosing regimen every 3 weeks, as opposed to standard 2 week dosing, confirmed in this patient over a 4 year follow up period. Cost analyses show that weight-based maintenance dosing costs 312,000 per year, while extending the dosing interval to every 3 weeks would cost 208,000, a savings of 104,000 per year, relative to the cost of 72,000 from more frequent eculizumab dosing during his initial hospitalization to suppress his acute disease. Conclusion: This case exemplifies the potential of severe, multisystem involvement of aHUS presenting with extra-renal manifestations, including rhabdomyolysis as in this case, and highlights the possibility for improved clinical outcomes and higher value care with individualized eculizumab dosing in patients over the course of their disease.